TRANS-HIS (Transformative–Historical Consciousness) Learning Model to Improve the Verstehen Abilities of High School Students in Lampung - Arif, Suparman; Sinaga, Risma Margaretha; Miswar, Dedy (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study develops and evaluates the effectiveness of the TRANS-HIS (Transformative–Historical Consciousness) learning model in enhancing high school students’ historical literacy and interpretive (verstehen) abilities in Lampung Province, Indonesia. Employing a Research and Development approach with a quasi-experimental non-equivalent control group design, the model was implemented and tested in two senior high schools (SMAN 2 Metro and SMA YP Unila Bandar Lampung). The model integrates transformative learning and historical consciousness frameworks grounded in cognitive-constructivist, psychosocial, field learning, independent learning, and andragogical perspectives to promote reflective, contextual, and empathetic historical learning. Quantitative data from pretest–posttest assessments and student response questionnaires were analyzed using descriptive and inferential statistics. Findings indicate a significant improvement in the experimental group’s learning outcomes, with mean scores increasing from 46.94 to 80.07 (N-Gain = 0.62; p < 0.001), compared to the control group’s increase from 46.81 to 65.21 (N-Gain = 0.30). Additionally, 81% of students reported that the TRANS-HIS model fostered more reflective, empathetic, and relevant learning experiences. These results demonstrate that integrating transformative pedagogy with historical consciousness effectively strengthens students’ interpretive competence beyond factual recall and supports meaningful engagement with historical values and contemporary contexts. The study contributes theoretically by operationalizing the integration of Weberian verstehen and transformative learning within a coherent instructional framework, and practically by providing a validated pedagogical model aligned with 21st-century history education, character formation, and reflective citizenship development.